PRACTICAL APPLICATION OF THE METHODOLOGY OF CONVERSION AND COMPARISON OF DIFFERENT CLASSIFICATION SYSTEMS OF ASSESSMENT OF MINERAL RESOURCES ON THE EXAMPLE OF DOMESTIC GRAPHITE AND COPPER DEPOSITS - LYTVYNIUK, Stanislav (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
Background. The analysis of practical application of comparison results by groups of classification features of mineral raw material assessment systems has applied and methodological significance. Methodological approaches to the harmonization (conversion) of various classification systems allow us to update the State Subsoil Fund of Ukraine according to criteria of the United Nations Framework Classification for Resources and identify promising investment directions at various stages of subsoil use. Methods. Considering the experience and results of the state expertise of geological and economic assessment materials for graphite and copper reserves and resources, a wide range of studies, which includes general scientific and special methods of scientific and applied research, has been conducted. In addition to general theoretical methods of analysis, statistics and systematization, a set of methods of geological and commercial characteristics of graphite and copper deposits has been used to achieve the goal. Results. The analysis of reserves and resources categories of the most widespread classification systems, which have a reliable bridging and harmonization, has been conducted. Harmonization (conversion) and comparison of different classification systems for the assessment of mineral resources has been performed for domestic graphite and copper deposits based on the European Union list of critical mineral raw materials. Research results suggest the development of a unified classification system for stakeholders (state, investor, society) in order to make decisions in the field of resource management at all levels. Conclusions. Presented methodological studies on the development of unified approaches to the assessment of reserves and resources accounted for by the State Balance provide an opportunity to determine the investment potential of undeveloped subsoil areas at the initial stages. Suggested mechanism for bringing the undistributed subsoil fund into compliance includes the harmonization of reserves, which are accounted for, with different classification systems according to three UNFC criteria: determination of the degree of geological knowledge (G-axis); the degree of feasibility study (F-axis); and commercial significance (E-axis).